2006
DOI: 10.1126/science.1126119
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Advance of Spring Arrival Dates in Long-Distance Migratory Birds

Abstract: Several bird species have advanced the timing of their spring migration in response to recent climate change. European short-distance migrants, wintering in temperate areas, have been assumed to be more affected by change in the European climate than long-distance migrants wintering in the tropics. However, we show that long-distance migrants have advanced their spring arrival in Scandinavia more than short-distance migrants. By analyzing a long-term data set from southern Italy, we show that long-distance mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
476
6
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 418 publications
(513 citation statements)
references
References 20 publications
28
476
6
3
Order By: Relevance
“…This fact prevented us from quantifying change in migration phenology in relation to local climate, because climate during any part of the migratory path could potentially affect change in phenology (44,45). Therefore, we analyzed change in phenology over time, assuming that such change was due to change in climate, as has been done in other studies (8,9,21,35,46,47). Changes in migration dates were the slope of the simple linear regression of migration date on year, expressed as days/year.…”
Section: Methodsmentioning
confidence: 99%
“…This fact prevented us from quantifying change in migration phenology in relation to local climate, because climate during any part of the migratory path could potentially affect change in phenology (44,45). Therefore, we analyzed change in phenology over time, assuming that such change was due to change in climate, as has been done in other studies (8,9,21,35,46,47). Changes in migration dates were the slope of the simple linear regression of migration date on year, expressed as days/year.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have investigated the impact on migrant species due to changing climate conditions along migration routes on stopover sites and wintering grounds (Tøttrup et al 2008). The potential impacts of climate change on the breeding ranges of European birds have been estimated recently (Huntley et al 2008), and changes in migration phenology have been reported in numerous species (Jonzén et al 2006). However, we still need to study the potential impacts on winter ranges.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence has mounted about its impacts on different groups of species and stages of a species lifecycle (Hughes, 2000;Parmesan, 2006). Especially for birds (Crick, 2004;Chambers et al, 2005;Leech and Crick, 2007;Wormworth and Mallon, 2007), climate change has been shown to induce poleward (Hitch and Leberg, 2007) and upward shifts of the distributional ranges (Pounds et al, 1999), to alter the timing of major seasonal events such as migration (Jenni and Kéry, 2003;Jonzen et al, 2006;Gordo, 2007) or egg laying (Crick and Sparks, 1999;Torti and Dunn, 2005;Both and te Marvelde, 2007) and to influence survival and productivity and hence, population dynamics (Sanz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%